Evaluating rodent motor functions: Which tests to choose?. (December 2017) - Schönfeld, Lisa-Maria; Dooley, Dearbhaile; Jahanshahi, Ali; Temel, Yasin; Hendrix, Sven
Highlights: For high quality results, sensitive behavioral tests for rodents should be used. Three major categories of rodent motor skill tests are reviewed and evaluated. Recommendations for choosing the best behavioral test are provided. Abstract: Damage to the motor cortex induced by stroke or traumatic brain injury (TBI) can result in chronic motor deficits. For the development and improvement of therapies, animal models which possess symptoms comparable to the clinical population are used. However, the use of experimental animals raises valid ethical and methodological concerns. To decrease discomfort by experimental procedures and to increase the quality of results, non-invasive and sensitive rodent motor tests are needed. A broad variety of rodent motor tests are available to determine deficits after stroke or TBI. The current review describes and evaluates motor tests that fall into three categories: Tests to evaluate fine motor skills and grip strength, tests for gait and inter-limb coordination and neurological deficit scores. In this review, we share our thoughts on standardized data presentation to increase data comparability between studies. We also critically evaluate current methods and provide recommendations for choosing the best behavioral test for a new research line.